Assessment for Learning Capacity of Secondary School Teachers in Ogun State, Nigeria - Ajayi , Olufemi Abiodun (African Journal of Education,Science and Technology (AJEST), 2013)
Assessment is an educational tool required for quality assurance and accountability on the part of teachers and school administrators amongst others. The public outcry with respect to dwindling performance of secondary school students in external examinations suggests a systemic failure and assessment is one significant component. Thus, this study examined the assessment for learning capacity of secondary school teachers in Ogun State, Nigeria. Survey research design was adopted for the study. The sample was 600 teachers from 24 selected junior and senior secondary schools that co-exist together in the same premises. Multistage sampling technique was used in selecting the sample from 6 Local Government Areas (LGAS) across the 3 Senatorial districts in the state. The only instrument used for data collection was “Teachers Need Assessment Questionnaire on Evaluation” (TNAQE) and it was developed and trial tested by the researcher and found to have .75 coefficient of internal consistency. The results show that secondary school teachers are grossly deficient in assessment practice with particular reference to use of assessment instruments and assessment report and record keeping. Inadequacies were also noticed in test construction capacities of these teachers. Results indicate further that a significant difference (t -value=-.5.624; p<.05) exists between assessment practices of male and female teachers, but non-significant differences was recorded for educational qualifications and years of teaching experience. Difference between expected mean and observed mean for test construction guidelines was significant (t-value = 20.084; p< .05), but insignificant for use of assessment instruments (t-value = -.1.728; p>.05) and assessment report and record keeping practice (t-value = 1.85; p>.05) by the teachers. Appropriate recommendations were made to reverse the ugly situation.